Eating Disorders and Obesity : A Counselor's Guide to Prevention and Treatment - Choate, Laura Hensley (Hoboken : American Counseling Association, 2013)
Both practical and comprehensive, this book provides a clearframework for the assessment, treatment, and prevention of eatingdisorders and obesity. Focusing on best practices and offering arange of current techniques, leaders in the field examine theselife-threatening disorders and propose treatment options forclients of all ages. This text, written specifically forcounselors, benefits from the authors' collective expertiseand emphasizes practitioner-friendly, wellness-based approachesthat counselors can use in their daily practice. Parts I and II of the text address risk factors in andsociocultural influences on the development of eating disorders,gender differences, the unique concerns of clients of color,ethical and legal issues, and assessment and diagnosis. Part IIIexplores prevention and early intervention with high-risk groups inschool, university, and community settings. The final sectionpresents a variety of treatment interventions, such ascognitive'behavioral, interpersonal, dialectical behavior,and family-based therapy.
Foundations. Sociocultural Influences on the Development of Eating Disorders and Obesity / Linda Smolak, Caitlin Chun-Kennedy -- Gendered Considerations in the Treatment and Prevention of Eating Disorders / Margo Maine, Douglas Bunnell -- Clients of Color and Eating Disorders: Cultural Considerations / Regine M Talleyrand -- Ethical and Legal Issues in Counseling Clients With Eating Disorders / Laura H Choate, Mary A Hermann, Leigh Pottle, Jodi Manton -- Assessment and Practice Frameworks for Eating Disorders and Obesity. Assessment and Diagnosis of Eating Disorders / Kelly C Berg, Carol B Peterson -- Assessment, Consultation, and Intervention for Eating Disorders in Schools / Jennifer Maskell Carney, Heather Lewy Scott -- Assessment, Conceptualization, and Intervention With Young Adult Women With EDNOS: A Framework for Practice / Alan M Schwitzer, Constance Rhodes -- Effective Prevention and Early Intervention for Eating Disorders and Obesity. Preventing Childhood Obesity / Janet A Lydecker, Elizabeth Cotter, Rachel W Gow, Nichole R Kelly, Suzanne E Mazzeo -- Prevention of Eating Disorders in Children: The Role of the Counselor / Niva Piran -- Eating Disorders Prevention With Adolescents and Young Adults / Heather Shaw, Eric Stice -- Effective Prevention Programs in College and University Settings / Deanne Zotter, Justine Reel -- Cognitive-Behavioral Therapy Guided Self-Help for Binge Eating: A Culturally Sensitive Minimal or Early Intervention Program / Fary M Cachelin, Munyi Shea, Frances A Bono -- Effective Treatments for Eating Disorders and Obesity. Enhanced Cognitive-Behavioral Therapy Approach to Counseling Clients With Eating Disorders / Anthea Fursland, Hunna J Watson -- Interpersonal Psychotherapy for Clients With Eating Disorders / Heather L Waldron, Marian Tanofsky-Kraff, Denise E Wilfley -- Psychosocial Treatments for Obesity and Aberrant Eating Patterns in Youths / Kerri N Boutelle, Stephanie Knatz -- Dialectical Behavior Therapy for Clients With Complex and Multidiagnostic Eating Disorder Presentations / Anita Federici, Lucene Wisniewski -- Family-Based Therapy for Children and Adolescents With Anorexia / Kim Hurst, Shelly Read -- A Relational-Cultural Approach to Working With Clients With Eating Disorders / Heather Trepal, Ioana Boie, Victoria Kress, Tonya Hammer.
Includes bibliographical references and index.
Description based on CIP data; resource not viewed.
Keywords: Eating disorders -- Treatment; Eating disorders -- Prevention; Obesity -- Treatment; Obesity -- Prevention; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Eating disorders -- Prevention; Eating disorders -- Treatment; Obesity -- Prevention; Obesity -- Treatment; Electronic books